2017
DOI: 10.2196/jmir.v20i2.8342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peer-Based Social Media Features in Behavior Change Interventions: Systematic Review

Abstract: Background: Incorporating social media features into digital behavior change interventions (DBCIs) has the potential to contribute positively to their success. However, the lack of clear design principles to describe and guide the use of these features in behavioral interventions limits cross-study comparisons of their uses and effects. Objective: The aim of this study was to provide a systematic review of DBCIs targeting modifiable behavioral risk factors that have included social media features as part of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A recent review of social media use in behaviour change interventions found that functions for peer grouping improved perceptions of social support and social support coping 20 . This reinforces the important role of social networking platforms in interventions to provide peer support rather than be restricted to delivery of information.…”
Section: Introductionmentioning
confidence: 79%
“…A recent review of social media use in behaviour change interventions found that functions for peer grouping improved perceptions of social support and social support coping 20 . This reinforces the important role of social networking platforms in interventions to provide peer support rather than be restricted to delivery of information.…”
Section: Introductionmentioning
confidence: 79%
“…To the best of our knowledge, no application has been identified for facilitating challenging misinformation online. Given that incorporating design approaches into digital behaviour change interventions is successful in many diverse areas (Elaheebocus et al 2018), design considerations can be extended to encourage users to disagree, question, or correct. As the persuasive system design model has been employed in a variety of methods to encourage behaviour change (Torning and Oinas-Kukkonen 2009) it offers an opportunity to motivate users to challenge misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…In each of these types, the over-arching characteristics include: connections and relationship-building, speedy delivery, and not limited by geography. Incorporating social media features into social behavior change activities has been shown to contribute positively to their success [72].…”
Section: Summary Of the Evidencementioning
confidence: 99%